Cephalanthera yintiaolingensis (Orchidaceae, Epidendroidee, Neottieae), a new mycoheterotrophic orchid from Northeast Chongqing, China - Chen, Feng; Xiong, Chi; Zheng, Chang-Bing; Jin, Xiao-Hua; He, Hai (Phytotaxa, 2023)
A new species of Orchidaceae, Cephalanthera yintiaolingensis, is described and illustrated from a nature reserve of Karst region in Northeast Chongqing, Southwest China. Morphologically, it is related to both C. exigua and C. subaphylla in habit and floral morphology. However, it differs from C. exigua by lip having obvious spur, flabellate middle lobe with five to seven lamellae, from C. subaphylla by lacking green blade in its sheath-like leaves, flabellate middle lobe, and obtuse apex in both sepals and petals. Cephalanthera yintiaolingensis was only found in type locality and was assessed as Data Deficient (DD).